2017
DOI: 10.1103/physreva.96.062111
|View full text |Cite
|
Sign up to set email alerts
|

Interference between two resonant transitions with distinct initial and final states connected by radiative decay

Abstract: The resonant line shape from driving a transition between two states, |a and |b , can be distorted due to a quantum-mechanical interference effect involving a resonance between two different states, |c and |d , if |c has a decay path to |a and |d has a decay path to |b . This interference can cause a shift of the measured resonance, despite the fact that the two resonances do not have a common initial or final state. As an example, we demonstrate that such a shift affects measurements of the atomic hydrogen 2S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…[7] and [8]. Such interference effects have been investigated by the present authors [9][10][11][12][13][14][15] and by others [16][17][18][19][20][21][22][23][24][25][26]. These investigations indicate that interference with a neighboring resonance, even if it is very distant, can lead to significant shifts for precision measurements.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…[7] and [8]. Such interference effects have been investigated by the present authors [9][10][11][12][13][14][15] and by others [16][17][18][19][20][21][22][23][24][25][26]. These investigations indicate that interference with a neighboring resonance, even if it is very distant, can lead to significant shifts for precision measurements.…”
Section: Introductionmentioning
confidence: 54%
“…When added in quadrature, the uncertainty from these three sources gives 20 kHz, and is dominated by the standard deviation of the 8 configurations. A final consideration is found in our previous work [15], in which we showed that the effect of higher-n states could be of the order of 10 kHz. Since the 20 kHz uncertainty assigned here is larger than the this 10-kHz scale, and since, as discussed in Ref.…”
Section: Corrected Centermentioning
confidence: 82%
See 1 more Smart Citation
“…One concern for the present measurement is the effect of other hyperfine transitions and transitions involving states with n ≥ 3. This concern is heightened by our analysis of unexpectedly large shifts from n = 3 states for Lamb shift measurements (15). It is also heightened because we still see 0.3% of our Lyman-a signal, even when we employ all six of the rf cavities shown in Fig.…”
Section: Effect Of Other Statesmentioning
confidence: 87%
“…Hessels and co-workers have made significant contributions toward understanding these effects [47,[56][57][58][59], and they have shown that measurements performed with an uncertainty comparable to the square of the linewidth divided by (twice) the separation of the main resonance and a neighboring (offresonant) transition may well be affected by them [55]. This "rule of thumb" [47], which has also been obtained analytically by other researchers using perturbation theory [60], gives an approximate value for the error one would obtain fitting a Lorentzian profile to a line shape distorted by QI effects.…”
Section: Quantum Interferencementioning
confidence: 99%